Ultrasonic non-destructive testing of plate-like structures using piezoelectric array transducers - Prado, Vander Teixeira [UNESP] (2014)
This thesis presents the study and implementation of non-destructive testing techniques of platelike structures using piezoelectric array transducers and guided acoustic waves, associated with beamforming techniques and image compounding methods. Damage detection in structures using guided waves and arrays is a promising research area, especially in the aerospace and energy fields, where the use of plate-like structures demands thorough inspection due to the high safety levels of operation. Guided acoustic waves techniques can be used to inspect relatively large areas without the necessity of moving the transducers, in a non-destructive way. There are different propagation modes that can be coupled to the plate, and each mode is sensitive to specific types of defects, like notches, delamination and surface defects. Wave propagation, different propagation modes and dispersion characteristics, as well as arrays characteristics and imaging algorithms, are studied. MATLAB and PZFlex simulations are used to get further insight in the theoretical aspects, to obtain dispersion curves, interaction with defects and array response. Experimental results validate the simulations with isotropic materials (aluminum). A 16-elements piezoelectric linear array is mounted at the border of an aluminum plate with artificial defects. The signals related to all combinations of transmit-receive pairs are obtained with burst excitation, for use with synthetic aperture (SA) techniques. The first contribution of this work is a method for defect detection based on the instantaneous phase of the aperture data. The instantaneous phase (IP) image is obtained by replacing the amplitude information by the instantaneous phase in the conventional SA beamforming. From the analysis of the IP image, a threshold level is proposed in terms of the number of signals used for imaging. This threshold is applied to the IP image, resulting ...